KAJIAN IDEOLOGI SENI RUPA 1990-AN: STUDI KASUS AGUS SUWAGE - Anggiat Tornado; Dadang Suganda; Setiawan Sabana; Reiza D. Dienaputra (Jurusan Seni Rupa ISBI Bandung, 2013)
The new minset, which evolves in society, becomes the minset held by all member of society, including the artists. However, differences show up in the progressing minset. The artists as the social and cultural agent have their own way to provide solution towards the differences thrpugh their creative works. The ideology of arts in the 1990’s tends to voice the injustice happening in the society using aesthetic language, the artists give criticisms to all member of society, from the state to the artists themselves. The progress of visual arts in thw 1990’s can eventually be concluded as having it’s own from and theme; it expresses the artists ideas more than their works. Agus Suwage who starter his career s painter prefer painting as his from of expression. Those who have been helped through his from of campaign posters are non-govermental organizations (Lembaga Swadaya Masyarakat/LSM) such as the Commission dor Disappearances and Victims of Violence Kontras (Komisi Nasional untuk Orang Hilang) and Indonesian. Legal Aid Foundation (LBHI/Lembaga Bantuan Hukum Indonesia) in his process of creative works, Agus Suwage tends to make himself as part of problem. He obtains a lot of information from mass media that finally influences his aesthetis works.Keywords: Ideology, Art in The 1990’s